The role of chemoprevention in cancer control - BUIATTI EVA (Instituto Nacional de Salud Pública, 1997)
Chemoprevention can be defined as the use of chemical compounds or medicines to prevent the occurrence of precancerous lesions (markers) or to slow down or revert the progression of clinically established disease. The use of randomized trial design is considered the gold standard for evaluating the preventive value of chemicals against cancer, since they control for confounding and avoid information bias. The principal school in relation to cancer control through chemoprevention is based on studies of cancer and diet. Initially, ecological studies set the cornerstone, but later case-control studies supported the hypothesis of an inverse association between foods and cancer risk (principally epithelial), suggesting that determined micronutrients participate as protection in this process. Other studies include specific chemical analyses, which have potential problems that could lead to erroneous conclusions, such as sample and measurement errors. During this decade randomized intervention trials have been carried out to test this hypothesis, but conclusions have been so diverse and the designs used have been so different in terms of levels of exposure, that consistent conclusions are not possible. We can conclude that using studies with randomized, double-blind, controlled designs is interesting, but problems remain to be solved, including: agent selection, the design to be chosen, and especially the balance between benefits sought and secondary effects, including cost-effectiveness, since some chemicals cannot compete with other preventive or therapeutic measures.